A Failure to Launch: Regulatory Modes and Boredom Proneness - Mugon, Jhotisha; Struk, Andriy; Danckert, James (Frontiers in Psychology, 2018)
Boredom is a ubiquitous human experience characterized as a state of wanting but failing to engage with the world. Individuals prone to the experience of boredom demonstrate lower levels of self-control which may be at the heart of their failures to engage in goal-directed, meaningful behaviours. Here we develop the hypothesis that distinct self-regulatory profiles, which in turn differentially influence modes of goal pursuit, are at the heart of boredom proneness. Two specific regulatory modes are addressed: Locomotion, the desire to ‘just do it’, an action oriented mode of goal-pursuit, and Assessment, the desire to ‘do the right thing’, an evaluative orientation towards goal pursuit. We present data from a series of seven large samples of undergraduates showing that boredom proneness is negatively correlated with Locomotion, as though getting on with things acts as a prophylactic against boredom. This ‘failure to launch’ that we suggest is prevalent in the highly boredom prone individual, could be due to an inability to appropriately discriminate value (i.e., everything is tarred with the same grey brush), an unwillingness to put in the required effort to engage, or simply a failure to get started. In contrast, boredom proneness was consistently positively correlated with the Assessment mode of self-regulation. We suggest that this association reflects a kind of rumination that hampers satisfying goal pursuit.